Effect of Cultural Heritage on Tourism Development in Italy - Galli, Antonio (International Journal of Modern Hospitality and Tourism, 2024)
Purpose: The aim of the study was to analyze the effect of cultural heritage on tourism development in Italy. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: The cultural heritage of Italy plays a significant role in its tourism development, attracting millions of visitors annually to historic cities like Rome, Florence, and Venice. Italy's rich history, art, architecture, and traditions make it a global cultural destination, with UNESCO World Heritage Sites such as the Colosseum, the Vatican, and the Uffizi Gallery serving as major draws. This cultural wealth not only boosts the tourism industry but also supports local economies and preserves historical landmarks. Unique Contribution to Theory, Practice and Policy: Cultural capital theory, sustainable tourism theory & heritage conservation theory may be used to anchor future studies on the effect of cultural heritage on tourism development in Italy. Implementing practical measures such as visitor quotas, dynamic pricing, and timed entry tickets can help regulate tourist flow to high-traffic cultural heritage sites. Policymakers should develop sustainable tourism frameworks that balance economic growth with cultural heritage preservation.